The viewpoints of early years practitioners on strategies to support children with speech, language and communication needs: a Q methodological study - Taylor, Jemma Elizabeth (2016)
Acquiring language is understood to be a key part of a child’s development (Siraj-Blatchford & Clarke, 2003), impacting skills including literacy and behaviour. The number of children identified as having speech, language and communication needs has been increasing by 4-6 percent each year since 2011 and is the most common primary need of children with on the SEN register (Whitaker, 2014). Early intervention is argued to have the greatest impact on the outcomes for children, as well as being the most cost-effective (Law et al., 2001). However, there has been a call to improve the provision for children with these needs due to the variability of the provision children receive (Bercow, 2008). Due to the diverse workforce, as well as the recognised importance of practitioners viewpoints, there has been a call for research into the viewpoints of early years practitioners regarding strategies to support children with SLCN (Marshall & Lewis, 2014). The present research uses a Q methodological research approach (Stephenson, 1953) to explore the viewpoints of 42 early years practitioners on strategies to support children with speech, language and communication needs. Q methodology utilises the advantages of both qualitative and quantitative research methods and creates open communication around complex topics in order to clarify participants’ views and explore subjective and diverse viewpoints. The data generated by Q methodology was analysed using a by-person factor analysis. Three distinct viewpoints were identified within the group of early years practitioners who participated in the research. These viewpoints were: • One: Tailor interventions and seek professionals’ advice • Two: Emphasis on stand-alone strategies, alter instructional language and don’t use visuals • Three: Understand a child’s background and utilise environmental strategies Follow-up interviews were carried out to strengthen the validity of the findings and explore what has informed the viewpoints captured, as well as to identify what helps and hinders practitioners working in line with their viewpoint. Numerous implications for professional practice have been identified that could support the effective implementation of strategies to support children with SLCN.